2023
DOI: 10.1002/phar.2796
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing prevention: Advances in pharmacotherapy for HIV prevention

Abstract: The HIV epidemic continues to pose a significant burden on the healthcare system.Although the incidence of annual new infections is decreasing, health disparities persist and most new infections remain concentrated into different racial, ethnic, and minority groups. Pre-exposure prophylaxis (PrEP), which involves those at high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…By contrast, extensive modifications of PF74 led to the development of lenacapavir ( LEN ) by Gilead Sciences, which demonstrated subnanomolar antiviral activity against numerous common HIV‐1 subtypes 17 . LEN has earned US Food and Drug Administration approval as a long‐acting anti‐AIDS drug 18,19 . However, due to the genetic heterogeneity of HIV, several drug‐resistant strains have been observed during LEN usage 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, extensive modifications of PF74 led to the development of lenacapavir ( LEN ) by Gilead Sciences, which demonstrated subnanomolar antiviral activity against numerous common HIV‐1 subtypes 17 . LEN has earned US Food and Drug Administration approval as a long‐acting anti‐AIDS drug 18,19 . However, due to the genetic heterogeneity of HIV, several drug‐resistant strains have been observed during LEN usage 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists play a crucial role in expanding access to and uptake of PrEP (Brizzi et al, 2023). This field is rapidly growing, and international studies conducted in the USA, Canada, Kenya, and South Africa (Cernasev et al, 2023;Greenwell et al, 2023;MacDonald et al, 2023;Mugo et al, 2017) have demonstrated the valuable contribution of pharmacists to PrEP scale-up.…”
Section: Introductionmentioning
confidence: 99%